ETA‐m‐PAN and its Composite Membrane with High Performance Prepared by In Situ Modification/NIPS Principle. Issue 4 (18th January 2019) - Qin, Yang; Wang, Yi‐Xing; Yang, Hu; Xu, Zhen‐liang
Abstract: Ethanolamine‐modified polyacrylonitrile (ETA‐m‐PAN) membrane is prepared by in situ modification integrated with a nonsolvent‐induced phase separation method for the first time. The results reveal that both the morphology and the separation performance of the modified membrane change greatly with condition parameters. The membrane formation mechanism is carefully investigated, which is related to the change in the molecular structure and hydrophilic property of ETA‐m‐PAN. The cross‐linked structure leads to the formation of ETA‐m‐PAN spongy membrane. The optimized condition parameters are determined by permeability‐selectivity analysis. Furthermore, the composite membrane with ETA‐m‐PAN as the selective layer is prepared by a dual‐casting method. The obtained membrane shows a good property, flux of 650L m −2 h −1 bar −1, 82% BSA rejection, and 84% water flux recovery ratio. This work demonstrates the great potential of this integrated method for new membrane preparation. Abstract : ETA‐m‐PAN composite membrane prepared by in‐situ modification and NIPS method.